The Botany and Chemistry of Hallucinogens. - Schultes, Richard (American Lecture Series; Publication No. 1025., 1980)
By Richard Evans Schultes, Harvard University, Cambridge, Massachusetts, and Albert Hofmann, Basel, Switzerland. With Forewords by I. Newton Kugelmass and Henrich Kluver. The Second Edition of this book encompasses all of the advances that have been made in this field since publication of the original text. Newly discovered hallucinogenic plants have been incorporated into the discussions along with new information on some well-known drugs. The authors continue to focus on the botany and chemistry of hallucinogens, although they also consider ethnobotanical, historical, pharmacological and psy.